Delineating the phenotype of 1p36 deletion in adolescents and adults. Issue 10 (8th July 2014) - Brazil, Ashley; Stanford, Kevin; Smolarek, Teresa; Hopkin, Robert
<x xml:space="preserve">Abstract</x> 1p36 deletion is the most common telomeric deletion syndrome, with an incidence of 1/5, 000–1/10, 000. A variety of clinical complications have been reported including seizures, hypotonia, heart malformations, cardiomyopathy, vision problems, and hearing loss. Approximately 90% are reported to have severe to profound intellectual disability and 75% to have absent expressive language. Little is known about long‐term outcomes. The current literature suggests a poor prognosis for most patients. This study attempted to assess medical conditions and function of adolescent and adult patients with 1p36 deletion. A survey was distributed through three support groups to identify patients >12 years of age to assess functional status and medical problems in older patients with 1p36 deletion syndrome. 40 patients were identified between 12 and 46 years old. Among our survey sample, medical complications including seizures, hypotonia, structural heart defects, hearing loss, and vision problems, were similar to previous reports. However, functional skills were better than anticipated, with an overwhelming majority reported to independently sit, walk, and receive the majority of nutrition orally. Forty‐four percent were reported to use complex speech abilities. While medical problems in patients with 1p36 deletion were similar to those that have been previously reported, we also demonstrated these same concerns persist into adolescence and adulthood. Additionally, patients were reported to have better functional skills than anticipated. Thus, quality of life and level of function appear to be better than anticipated from previous studies. © 2014 Wiley Periodicals, Inc.